2015
DOI: 10.1590/0037-8682-0059-2015
|View full text |Cite
|
Sign up to set email alerts
|

New predictors of malignant ventricular arrhythmias in Chagas disease: searching for the holy grail

Abstract: (Carlos Chagas, 1916) (1) Since the fi rst descriptions of Chagas disease (ChD), sudden death is considered one of the characteristics and responsible for >50% of the mortality in chagasic patients with heart failure. In this issue of RSBMT, Barbosa et al (2) . highlight several important aspects of the pathogenesis, prognosis, and treatment of ventricular arrhythmias in ChD (2) . Chagas disease has an essentially arrhythmogenic nature characterized by dense and complex ventricular arrhythmias; therefore, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…The complex physiopathology that is characteristic of the disease includes processes of progressive neuronal depletion, persistent myocardial fibrosis, and consequent cardiac remodeling with neurohormonal activation and an increase in serum catecholamine levels, generating important substrates for arrhythmogenesis and resulting in a poorer prognosis compared to other cardiomyopathies. [7][8][9][10][11] In the present study, the progressive increase in the number of PVCs/24 hours found as a function of the increase in risk category gives further strength to this mechanistic model of an important association between ventricular arrhythmias and mortality in chronic Chagas cardiomyopathy. Nevertheless, it was impossible to demonstrate the role of the phenomenon of dysautonomia, as evaluated according to HRV, in this process.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The complex physiopathology that is characteristic of the disease includes processes of progressive neuronal depletion, persistent myocardial fibrosis, and consequent cardiac remodeling with neurohormonal activation and an increase in serum catecholamine levels, generating important substrates for arrhythmogenesis and resulting in a poorer prognosis compared to other cardiomyopathies. [7][8][9][10][11] In the present study, the progressive increase in the number of PVCs/24 hours found as a function of the increase in risk category gives further strength to this mechanistic model of an important association between ventricular arrhythmias and mortality in chronic Chagas cardiomyopathy. Nevertheless, it was impossible to demonstrate the role of the phenomenon of dysautonomia, as evaluated according to HRV, in this process.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, unlike the case with other cardiomyopathies, in chronic Chagas cardiomyopathy, individuals with preserved LVEF are still at a risk of death from arrhythmia, a risk that is under-quantified when evaluated only according to the conventional prognostic markers, as shown on some occasions by the finding of a low Rassi score in individuals who went on to die from sudden cardiac death. 7,8,10,11 These considerations highlight the need to improve the risk stratification model by identifying other predictive factors, including those associated with dysautonomia, in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[97] Primary or secondary prevention should be a routine indication for patients with Chagas disease with malignant arrhythmias. [98] The combination of ablation procedures, amiodarone and/or beta-blockers might be considered in special cases to reduce the number of automatic ICD therapies, as in other types of cardiomyopathy. [99]…”
Section: Invasive Treatment Of Cardiovascular Chagas Diseasementioning
confidence: 99%